Application Status and Development Prospect of Coil Tubing Based on Logging Technology - ZHOU Yang; NIU Buneng; WANG Zhuo; ZHANG Zhijiang; DU Xu; JIANG Long; LIU Ping (Cejing jishu)
With the further development of unconventional oil and gas, the application of coiled tubing in logging has gradually increased, but it still faces challenges such as overlap between logging operations and downhole operations, unclear application direction, lack of technical features, and small application scale. This paper provides an in-depth analysis of the current application status of coiled tubing in logging, systematically sorts out the key factors restricting coil tubing technology development, and combines the current background of large-scale development of unconventional oil and gas to discuss the solution strategies in the main aspects of key technology breakthrough, logging process improvement, application scenario expansion, optical fiber logging system optimization, digital team construction, and optical fiber logging interpretation model construction. It emphasizes the importance of developing coiled tubing fiber logging technology and puts forward its potential value in improving operation efficiency and promoting geological engineering integration. It is pointed out that meeting the demand of unconventional oil and gas resources development and establishing coiled tubing technology with a well-matched logging operation mode and logging specific features is the key direction of future coiled tubing logging technology development, which will provide solid technical support for the efficient and safe development of oil and gas fields.